Meningkatkan Semangat Belajar dan Motivasi Siswa Melalui Platform Gamifikasi Quizizz dan Refleksi Pembelajaran Digital Berbasis Google Form: Penelitian - Arfiany Nur Amalia; I Nyoman Ruja (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research utilizes digital applications as a learning tool, with the main objective of increasing students' enthusiasm and motivation to learn. In the process, the Quizizz gamification platform and digital reflection through Google Form are used. Research activities were carried out in class 7.1 SMP Negeri 14 Malang in the subject of Social Science, with a focus on Social and Cultural Diversity in community life. The method applied is Classroom Action Research (PTK) which consists of two stages and involves 33 students as research subjects. Data collection methods in this study included observation, tests, questionnaires, and documentation, while the data analysis process was carried out with the help of IBM SPSS Statistics version 30 software. The results showed that the use of Quizizz was able to create an interactive and competitive learning atmosphere, increasing student enthusiasm and enthusiasm. Meanwhile, Google Form-based digital learning reflection helps students evaluate their learning experience, increase intrinsic motivation, and metacognitive awareness. A total of 91.52% of students were declared complete in working on LKPD, 53,3% of students felt excited and challenged to take part in Quizizz, and 66,7% of students stated that playing Quizizz was the most exciting part of learning.